Water and energy fluxes during summer in an arid‐zone passerine bird. (7th August 2015) - Smit, Ben; McKechnie, Andrew E.; Schoech, Stephan
<x xml:space="preserve">Abstract</x> Endothermic animals resident in hot, arid terrestrial environments are likely to face a trade‐off between their ability to obtain water and elevated thermoregulatory water requirements. We assessed whether daily water flux (DWF) is higher on hot days, reflecting increases in evaporative cooling demands, in an arid‐zone bird that obtains its water through food intake. We obtained measurements of DWF (partitioned into water influx and efflux rates) in 71 White‐browed Sparrow‐Weavers Plocepasser mahali at a desert site and a semi‐desert site, during summer in the Kalahari Desert of southern Africa. We found no evidence that DWF varied with maximum daily air temperature (Tair, range = 27.6–39.2 °C). Instead, DWF was lower during dry periods than in the wet season at the semi‐desert site. Furthermore, birds showed deficits in water balance (water influx/water efflux) during the dry periods at both sites. Our data show that DWF is low in a non‐drinking bird that obtains its water through food, and that demands for evaporative water loss on very hot days (maximum Tair of 40–44 °C) may exceed water intake rates during hot and dry periods. Species that do not have opportunities to drink will experience strong trade‐offs between thermoregulation, hydration state and activity levels as temperatures increase.